1996
DOI: 10.1021/la960119e
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Si−O Vibrations of Smectite Layers Accompanying the Sorption of Interlayer Water

Abstract: The frequencies of Si-O stretching, νSi-O, in layers of montmorillonite and of H-O-H bending, ν2, in the interlayer water were investigated by infrared spectroscopy. Oriented gels of Li-and Na-montmorillonite equilibrated at different water contents, mw/mc, were obtained by using a miniature pressure membrane apparatus. One part of each gel was used for the gravimetric determination of mw/mc. The other part was transferred to an FTIR spectrometer where the spectrum of the gel was measured by attenuated total r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
98
2
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(121 citation statements)
references
References 37 publications
20
98
2
1
Order By: Relevance
“…The reduction of structural Fe also increases the surface-charge density of the clay (Stucki, 1988;Stucki and Tessier, 1991;Gates et al, 1993;Yan and Stucki, 1999), causing the Fe(II)-bearing smectites to acquire a strong nucleophilic character that facilitates the transformation of chlorinated alkanes. The high concentration of H20 relative to that of 5CA, and the fact that smectite surfaces hydrate (Yan et al, 10 ...... 1996b, 1996cYan and Stucki, 1999), suggest that H20 molecules mediate the hydrogen bridging and the long-range interactions between 5CA and the clay surface ("outer sphere complex"; Wilkins, 1991). The formation of tetrachloroethene (4CE) is explained by the dehydrochlorination of 5CA (Roberts and Gschwend, 1991;Cervini-Silva et al, unpubl.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of structural Fe also increases the surface-charge density of the clay (Stucki, 1988;Stucki and Tessier, 1991;Gates et al, 1993;Yan and Stucki, 1999), causing the Fe(II)-bearing smectites to acquire a strong nucleophilic character that facilitates the transformation of chlorinated alkanes. The high concentration of H20 relative to that of 5CA, and the fact that smectite surfaces hydrate (Yan et al, 10 ...... 1996b, 1996cYan and Stucki, 1999), suggest that H20 molecules mediate the hydrogen bridging and the long-range interactions between 5CA and the clay surface ("outer sphere complex"; Wilkins, 1991). The formation of tetrachloroethene (4CE) is explained by the dehydrochlorination of 5CA (Roberts and Gschwend, 1991;Cervini-Silva et al, unpubl.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research revealed that the structure of the layer lattice Si-O vibrations are modified by interaction with and are coupled to the structure of the interlayer water (3). These mutual structural modifications at the clay-water interface evidently are insensitive to the type or concentration of monovalent electrolyte surrounding the mont-morillonite layers (4).…”
Section: Introductionmentioning
confidence: 99%
“…Infrared spectroscopic evidence indicates that interlayer water is strongly coupled to the clay-mineral surface (Yan et al, 1996a(Yan et al, , 1996b(Yan et al, , 1996c. The bond energy of Si-O in the tetrahedral sheet of the clay is modified by the interlayer H20 content, and is independent of the inorganic univalent cation in the interlayer.…”
Section: Introductionmentioning
confidence: 99%